Creativity landscapes: Systematic review spanning 70 years of creativity interventions for children - Alves-Oliveira, P. (2022)
Creativity plays a central role in children’s development and well-being, being considered a crucial skill to thrive in their personal and professional lives. Given its importance, researchers and educators highlighted the need to enhance creativity in individuals across the lifespan. However, it is crucial to understand how interventions and programs can promote creativity from an early age. The goal of this systematic review was to collect, summarize, and present evidence on research about nurturing creativity in children of elementary school age (5–13 years old), by systematically reviewing publications from 1950 to 2020, spanning 70 years of research. We additionally contributed to a classification system for characterizing creativity research by expanding on an existing coding scheme for creativity. This review resulted in the profiling of existing training that stimulates creativity in children. We discuss the results taking into account possible implications for practice and policymaking and future research directions in creativity research.